2021
DOI: 10.1088/1757-899x/1090/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Height and Surface Roughness of a Broad Crested Weir on the Discharge Coefficient: Experimental Study

Abstract: Weir is usually incorporated as control or regulation devices in hydraulic systems, with flow measurement as their secondary. It is normally intended for use in the field and thus to regulate broad discharges. Broad-Crested weir is among the oldest common weir types. In this paper, the effect of height and surface roughness for different Board Crested weirs models were studied on discharge coefficient (Cd) in a horizontal open channel. In the crest of the weir, certain materials may be combined with concrete (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hager and Schwalt [6] Bos [3] Rao and Muralidhar [11] Azimi and Rajaratnam [12] 0.1< (h / L) < 0.4 Doeringsfeld and Barker [13] Khosrojerdi, Kavianpour [9] Felder and Chanson [14] 0.02 <h/L < 0.3 Salmasi, Poorescandar [15] h/L≤0.27…”
Section: Researcher Name (Year)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hager and Schwalt [6] Bos [3] Rao and Muralidhar [11] Azimi and Rajaratnam [12] 0.1< (h / L) < 0.4 Doeringsfeld and Barker [13] Khosrojerdi, Kavianpour [9] Felder and Chanson [14] 0.02 <h/L < 0.3 Salmasi, Poorescandar [15] h/L≤0.27…”
Section: Researcher Name (Year)mentioning
confidence: 99%
“…Bazin [10] proposed and examined broad-crested weir for the first time after that; other researchers continue his approach as well [11,12]. Singer [13][14][15] showed that discharge coefficient is a function of elevation changes of weir (P) and its length (L). Hager and Schwalt [16,17] studied a more detailed on the hydraulic rectangular broad-crested weir.…”
mentioning
confidence: 99%